Hydrogen Atom Transfer Driven Enantioselective Minisci Reaction of Alcohols. Issue 25 (27th April 2022) - Colgan, Avene C.; Proctor, Rupert S. J.; Gibson, David C.; Chuentragool, Padon; Lahdenperä, Antti S. K.; Ermanis, Kristaps; Phipps, Robert J.
Abstract: Catalytic enantioselective Minisci reactions have recently been developed but all instances so far utilize α‐amino radical coupling partners. We report a substantial evolution of the enantioselective Minisci reaction that enables α‐hydroxy radicals to be used, providing valuable enantioenriched secondary alcohol products. This is achieved through the direct oxidative coupling of two C−H bonds on simple alcohol and pyridine partners through a hydrogen atom transfer (HAT)‐driven approach: a challenging process to achieve due to the numerous side reactions that can occur. Our approach is highly regioselective as well as highly enantioselective. Dicumyl peroxide, upon irradiation with 390 nm light, serves as both HAT reagent and oxidant whilst selectivity is controlled by use of a chiral phosphoric acid catalyst. Computational and experimental evidence provide mechanistic insight as to the origin of selectivity, revealing a stereodetermining deprotonation step distinct from the analogous reaction of amide‐containing substrates. Abstract : An enantioselective Minisci reaction between pyridines and prochiral α‐hydroxy radicals has been developed. Hydrogen atom transfer is used to generate the latter from simple alcohols and the reaction formally constitutes the couple of two C−H bonds to form a new C−C bond in a process that is highly enantioselective and regioselective. Computational studies provide insight into the origins of selectivity.